2021
DOI: 10.3389/fmed.2021.747678
|View full text |Cite
|
Sign up to set email alerts
|

TAFRO Syndrome in a Kidney Transplant Recipient That Was Diagnosed on Autopsy: A Case Report

Abstract: A 57-year-old man who received a kidney transplant 4 years previously owing to unknown underlying disease presented with thrombocytopenia and fever. Hepatosplenomegaly and lymphadenopathy were observed, and development of prominent anasarca and worsening of renal function yielded the diagnosis of TAFRO syndrome. He was treated with high-dose steroids and plasmapheresis, and a thrombopoietin receptor agonist was administered for refractory thrombocytopenia. However, his general condition worsened, and he died o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Electron microscopy showed loss of mesangial structures with subendothelial space enlargement, endothelial cell swelling, and loss of fenestra. The renal pathological findings reported by Mizuno et al were similar to those reported in previous case reports [ 5 8 ]; however, in our study, arteriolar myocyte vacuolization was newly reported as a characteristic renal pathological finding in TAFRO syndrome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Electron microscopy showed loss of mesangial structures with subendothelial space enlargement, endothelial cell swelling, and loss of fenestra. The renal pathological findings reported by Mizuno et al were similar to those reported in previous case reports [ 5 8 ]; however, in our study, arteriolar myocyte vacuolization was newly reported as a characteristic renal pathological finding in TAFRO syndrome.…”
Section: Discussionsupporting
confidence: 92%
“…There are a few reports on the renal pathological features of TAFRO syndrome. In previous case reports, the renal pathology of TAFRO syndrome included TMA [ 5 8 ] or membranous proliferative glomerulonephritis (MPGN) [ 9 , 10 ]. Patients with relatively early renal biopsy tended to have TMA, while those with late renal biopsy tended to have MPGN, suggesting that MPGN lesions in TAFRO syndrome result from chronic TMA lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mBP tended to increase after TPE, suggesting an improvement in circulatory dysfunction. Past studies reported a decrease in ADAMTS13 activity, which is crucial for fibrinolysis, in three cases with TAFRO syndrome [11,12,14]. TPE can also replenish ADAMTS13, which may improve disease status in these patients.…”
Section: Discussionmentioning
confidence: 88%
“…However, TPE was performed in all cases at our hospital, suggesting that pharmacotherapy alone is often unable to control the disease activity of TAFRO syndrome. To investigate the effects of TPE on TAFRO syndrome, we summarized the past 10 case reports of patients who underwent TPE for TAFRO syndrome in Table 2 [8][9][10][11][12][13][14][15][16]. Similarly, in our case series, TPE was not performed alone but in combination with various drug treatments in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although cyclosporine A has been widely used in the treatment of TAFRO syndrome [13], information regarding cases treated using tacrolimus remains limited. To the best of our knowledge, only four studies have reported the use of tacrolimus treatment for TAFRO syndrome [20,38,55,56] (Table 2), excluding one in which the duration of tacrolimus use was markedly short to evaluate its efficacy [33]. Among these studies, we first described two cases of TAFRO syndrome that were successfully treated using tacrolimus [20].…”
Section: Rituximabmentioning
confidence: 99%